Fisheries ecololgy and management of the Jaraqui (Semaprochilodus Taeniurus, S. Insignis) in central Amazonia - de Brito Ribeiro, Mauro Cesar Lambert; Junior, Miguel Petrere [UNESP] (Wiley, 1990)
The decline of heavily exploited stocks of large, high quality, food fishes in central Amazonia has led to increasing fishing pressure on smaller taxa, especially the jaraqui (Semiprochilodus spp.). The Prochilodontids, now the most important species to the fisheries, are seined by commercial fishermen during three distinct peridos. At the beginning of the annual floods, schools of mature jaraquis in poor‐water tributaries migrate downstream to spawn in the nutrient rich white‐water rivers. During these rapid spawning runs, fishing effort is concentrated in the lowermost reaches of the tributaries. After spawning, they return in small groups to feed intensively in the flooded forest of the same tributaries from which they had migrated. This period, of approximately three months, may be considered as a natural closed season to the fisheries. The dispersal migration is most complex and requires distinct fishing strategies. In the middle of the floods large schools of fat jaraqui descend from the tributaries to the white‐water rivers again. From there, they move upstream to different poor‐water tributaries. As downstream movements are more diffcult to observe, fishermen remain at fixed fishing grounds. This contrasts with the dynamic strategies of the subsequent upstream fishing period which contributes 60 per cent of the annual catches. Fluctuations in catch are shown to reflect year to year variations in abundance, which are linked to the hydrological cycle. Considering that fishing over the stocks of jaraqui has already more than compensated for the deficit in catch of larger species, a combination of increased effort and environmental problems could lead, in a short period to a depletion of one of the most profitable fisheries of central Amazonia. Regulation of the fisheries could benefit from a more reasonable distribution of effort among other migratory illiophagous species which remain unexploited, if the goal of sustainable yield and conservation of these stocks is to be achieved. Reserved waters in large strategic units of at least 300 km along white‐water rivers (which is equivalent to the maximum upstream displacement of jaraqui during their dispersal migrations) could also be useful to compensate for the loss of floodplain areas due to deforestaion, river regulation, use of pesticides, and mining. River impoundments in tributaries in central Amazonia may have little effect on jaraqui stocks, as spwning movements are unlikely to be directly interrupted by dams. However, alterations of the hydrological regime may also benefit from simulation of the flood cycle to mitigate potential negative impacts. Copyright © 1990 John Wiley & Sons, Ltd
Keywords: Amazonia; Fisheries; Management of fish stocks; Semaprohilodus